Modeling of a functionally graded material (FGM) subjected to mechanical loading - Hoong, Pei Yu. (2009)
This report describes a finite element analysis of a Functionally Graded Material (FGM) subjected to mechanical loading for the estimation of the effective thermo-physical properties based on two commercial programs; a FE program (ANSYS) and spreadsheet software (EXCEL). A FGM is a composite, consisting of two or more phases, which is fabricated such that its composition varies in some spatial direction. Two pure substances that make up the composite are namely Ceramic (ZrO2 – 8%Y2O3) and Nickel Alloy (NiCoCrAlY). These materials are to be randomly distributed in a model and analyzed.